Characterize a typically Dscam with alternative splicing in mud crab Scylla paramamosain. Issue 71 (December 2017) - Li, Wenshi; Tang, Xixiang; Chen, Yan; Sun, Wanwei; Liu, Yan; Gong, Yi; Wen, Xiaobo; Li, Shengkang
Abstract: As a member of the immunoglobulin superfamily, Down syndrome cell adhesion molecule (Dscam) could function in the innate immunity of invertebrates. Recently, it is shown that arthropod Dscams play similar functions as antibodies in the adaptive immune system. Dscam could produce thousands of isoforms by alternative splicing and specifically bind to various pathogens. In the present study, we cloned the first Dscam from mud crab Scylla paramamosain ( Sp Dscam), with full-length cDNA 7363 bp containing an open reading frame (ORF) of 6069bp and encoding 2022 amino acids, which had typical domain architecture as other arthropods, i.e., 10 immunoglobulin domains (Ig), 6 fibronectin type 3 domains (FN III), transmembrane and cytoplasmic tail. Quantitative real-time PCR revealed that Sp Dscam was highly expressed in brain, skin, muscle, intestine and hepatopancreas, but weakly expressed in hemolymph, heart and gill. Sp Dscam had three alternative splicing regions, located at the N-terminal of Ig2 and Ig3 as well as on the whole Ig7. In these regions, 32, 41 and 14 exons were detected, together with the two exon types of transmembrane domain, indicating Sp Dscam could potentially encode at least 36, 736 unique isoforms. Sp Dscam induced by Vibrio parahaemolyticus challenge had strong binding ability to V. parahaemolyticus . Further, Sp Dscam induced by V. parahaemolyticus possessed a clearance of V. parahaemolyticus in S. paramamosain . Collectively, the results indicated Sp Dscam was a hypervariable pattern-recognition receptor (PRR) by alternative splicing in innate immunity system of mud crab S. paramamosain . Highlights: Full-length of Sp Dscam with 7363 bp was isolated from mud crab. At least 36, 736 potentially unique isoforms by alternative splicing was produced. A Sp Dscam isoform has a specific binding and clearance ability to specific pathogen.